Real role of an ultrafiltration hollow-fibre membrane module in a submerged membrane bioreactor - Ünlü, A; Hasar, H; Kinaci, C; Çakmakci, M; Koçer, NN (Elsevier, 2005)
This paper presents the real role of UF membrane modules with a 0.03 mu m pore size used in a submerged membrane bioreactor on effluent quality parameters. For this purpose, the values of effluent and mixed liquor for some parameters were determined at different operational periods. It was shown that the biochemical reactions in the bioreactor have a greater role than the separation of the membrane module on the removal of organic and nutrient pollutants. Inert COD was not removed by the system. Orthophosphate, ammonium and nitrate ions were respectively removed on the levels of 30%, less than 10% and 28% on average. It was considered that the removal ratios of these parameters were affected only by the concentrated activated sludge process and occurring under a place to place anoxic condition.
Keywords: submerged membrane bioreactor; ultrafiltration; module capacity and removal